2020
DOI: 10.3389/fonc.2020.565582
|View full text |Cite
|
Sign up to set email alerts
|

Review of Atypical and Anaplastic Meningiomas: Classification, Molecular Biology, and Management

Abstract: Although the majority of meningiomas are slow-growing and benign, atypical and anaplastic meningiomas behave aggressively with a penchant for recurrence. Standard of care includes surgical resection followed by adjuvant radiation in anaplastic and partially resected atypical meningiomas; however, the role of adjuvant radiation for incompletely resected atypical meningiomas remains debated. Despite maximum treatment, atypical, and anaplastic meningiomas have a strong proclivity for recurrence. Accumulating muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 146 publications
1
56
0
1
Order By: Relevance
“…Most agree that there is no role for RT for WHO grade I tumors, unless in the setting of unresectable symptomatic initial or recurrent tumors. While the role of radiotherapy in WHO grade II GTR tumors not fully elucidated, multiple phase II and randomized controlled trials are trying to shed light on this issue [ 116 ]. A phase II trial (RTOG 0539) demonstrated that their intermediate risk group (newly diagnosed WHO grade II GTR (69.2%) and recurrent WHO grade I with any resection extent (30.8%)), when treated with RT (standard dose of 54 Gy), had a 98.3% 3-year progression-free survival (PFS) and 96% 3-year overall survival (OS) ( Table 6 ) [ 117 ].…”
Section: Current Areas Of Researchmentioning
confidence: 99%
“…Most agree that there is no role for RT for WHO grade I tumors, unless in the setting of unresectable symptomatic initial or recurrent tumors. While the role of radiotherapy in WHO grade II GTR tumors not fully elucidated, multiple phase II and randomized controlled trials are trying to shed light on this issue [ 116 ]. A phase II trial (RTOG 0539) demonstrated that their intermediate risk group (newly diagnosed WHO grade II GTR (69.2%) and recurrent WHO grade I with any resection extent (30.8%)), when treated with RT (standard dose of 54 Gy), had a 98.3% 3-year progression-free survival (PFS) and 96% 3-year overall survival (OS) ( Table 6 ) [ 117 ].…”
Section: Current Areas Of Researchmentioning
confidence: 99%
“…There are no other established therapy options and especially, more aggressive meningiomas are challenging to treat. After multiple rounds of resection and radiation there is no established treatment alternative to oppose further disease progression, while individualized treatment approaches are frequently offered [8].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO classification is an important prognostic tool that is based on histological criteria, but cannot fully predict tumor progression. There is substantial variation within the same grade among tumors, with studies reporting indolent behavior with no progression in up to 71% of AM cases ( 3 ). Therefore, it is especially important to accurately predict tumor progression and realize hierarchical tumor management.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the efficacy and neurotoxicity of radiotherapy, it is still controversial as to whether PORT is necessary as a routine treatment for AM. Based on the existing evidence, PORT is recommended for AM with STR, especially for skull base meningiomas ( 3 , 50 ). However, the role of PORT in patients with completely resected AM remains undefined, and there is still no unified consensus on whether these patients need radiotherapy, or the dose of radiotherapy ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation